Experimental investigation into the influences of pontoon and column configuration on vortex-induced motions of deep-draft semi-submersibles. (1st September 2016) - Liu, Mingyue; Xiao, Longfei; Lu, Haining; Shi, Junqi
Abstract: Deep-draft design of semi-submersibles improves vertical motions but leads to critical vortex-induced motions (VIM) attributable to fluctuating loads on columns. As characteristic components, both columns and pontoons produce complex wake interference and thus have significant influences on the VIM of semi-submersibles. This paper presents an experimental study on VIM of deep-draft semi-submersibles (DDS) to examine the effects of pontoons and column configuration. There were four test models including four-pontoon DDS, two-pontoon DDS, four-square-column structure and four-rhombic-column structure with no pontoons. A number of current headings and reduced velocities were considered. The main results reveal that the two-pontoon DDS can generate larger lift forces in comparison with the four-pontoon DDS; consequently, the transverse motion amplitudes at high reduced velocities are larger. However, the four-square-column structure with no pontoons shows the most significant transverse and yaw responses owing to the largest excitation forces induced by the well-established wake. On the other hand, similar trend and values in the transverse response are observed for the four-square-column structure at the 45° current heading and for the four-rhombic-column structure at the 0° current heading. The incidence angle related to columns has more significant effect on the VIM of DDS than that related to the platform. Highlights: Experimental studies on VIM for four DDS models are performed. We investigate the influences of pontoon and column configurations on VIM. Motion responses, excitation loads, and spectral characteristics are discussed. Pontoons can disturb the wakes of columns and consequently mitigate VIM behaviour. Column configuration shows significant effects on VIM at different current headings.